Mapping Vasculature and Nerve Networks in the Canine Skeleton: A Tool for Veterinary Anatomy Education and Learning - Amit Challana,; Jyoti Saini,; Om Prakash Choudhary, (Indian Journal of Veterinary Anatomy, 2026)
The skeletal system of dogs provides essential structural support, protects vital organs, and facilitates movement. One nondescript adult dog cadaver was used as animal material in this study. The cadaver was mascerated to collect the bones. Holes were drilled on the articular surfaces of bones to form the skeleton. Thick Nylon thread of three colors viz; red, blue and yellow were used to demonstrate the major arteries (red color), major veins (blue color), and major nerves (yellow color) on the dog skeleton. This teaching model explores the normal blood vessels and nerve patterns that permeate the Canis lupus familiaris skeletal framework, highlighting their roles in various functions of the body. The development of effective teaching tools is crucial in veterinary education, particularly when studying complex anatomical systems, such as the vascular and nervous networks. The study presents the development and evaluation of a life-sized Canis lupus familiaris skeleton model that visually and accurately maps the major blood vessels and nerve networks. The model is designed to serve as an educational tool, enhancing students' understanding of these intricate systems in veterinary anatomy courses.